Literature mapping: A bird's eye view on classification of factors influencing project success - Abdullah, A.A.; Rahman, H.A.; Harun, Z.; Alashwal, A.M.; Beksin, A.M. (Academic Journals, 2010)
The subject of project success has caught the attention of researchers for the last five decades. The long list of project success factors indicates that there are no common denominators for project success. It also indicates that there was no agreement on the definition of success. The aim of this review paper is to classify relevant literature on project success in order to obtain a greater breadth on this topic. This paper distinguishes the success of project into project success definition, measurement or dimension of project success, traditional success factors, non-traditional success factors, frameworks and models of project success, type of industry, location (country) of research, specific level (individual, group, organisation, and project), and phases of project (project life cycle). This paper further highlights the classification of the success factors of project in construction industry and other industries. The outcome of this paper is a literature review mapping, which provides a holistic picture of this notion to clearly specify the gap in literature.